Development and evaluation of a chemical kinetics reaction mechanism for tetramethylsilane-doped flames. (14th December 2019) - Janbazi, H.; Karakaya, Y.; Kasper, T.; Schulz, C.; Wlokas, I.; Peukert, S.
Graphical abstract: Highlights: Investigation of TMS-doped low-pressure H2 /O2 /Ar flames by MBMS. Development of a chemical reaction mechanism for TMS oxidation. Calculation of thermodynamics data of Si-containing species. Rate coefficient estimations by algorithmic optimization and analogies. Evaluation of the reaction mechanism against new experimental data. Abstract: Tetramethysilane (TMS) is a precursor for flame synthesis of silica (SiO2 ) nanoparticles. A chemical reaction mechanism was developed for the oxidation of TMS in a lean low-pressure ( p ≈ 30 mbar) H2 /O2 /Ar flame using species mole fractions, obtained from molecular-beam mass spectrometry (MBMS) measurements in a matrix-supported flat flame doped with 600 ppm TMS. The thermodynamic data of Si-containing species were determined from quantum-chemical calculations at the G4 level of theory. The formation and subsequent consumption of Si(OH)4, one of the main products of TMS oxidation, and the formation of Si4 O10 H4 clusters are hypothesized to be the primary pathway in the synthesis of silica nanoparticles. The reaction rate coefficients are either estimated via an algorithmic optimization procedure or are assumed based on analogies to similar reactions in the literature. The mechanism was further validated based on MBMS measurements with the same base flame doped with 400 and 800 ppm TMS.